THE REACTIONS OVER EMPLOYEE ENGAGEMENT THAT VIEWED FROM COMPENSATION,ORGANIZATIONAL JUSTICE AND WORK-LIFE BALANCE AND MEDIATED BY JOB SATISFACTION VARIABLE AT BRI BANK KEMAYORAN BRANCH - Wachyuni, Intan; Bohlen Purba, Charles (Dinasti International Journal of Management Science, 2020)
The aim of these research was to discover the main influence factors to employee engagement, Such as: compensation, organizational justice, work life-balance and job satisfaction. This research also wants to know the role of mediation satisfaction on the effect of compensation, organizational justice, work life-balance towards employee engagement. The research method by quantitative explanatory with SEM-PLS. The research sample was 98 BRI Bank Kemayoran Branch employees. Those sampling technique used saturated sampling (census). The results showed that compensation, organizational justice has an influence over job satisfaction, while work life-balance does not relate to it. Work-life balance, organizational justice and job satisfaction has affect towards employee engagement, while compensation does not affect those employee engagement. In addition, job satisfaction could mediates the effect of compensation and organizational justice variables on employee engagement, while not on the effect of work life-balance on employee engagement.